Physiological responses of oregano plants (Origanum vulgare L.) cultivated under colored meshes and with organic fertilizers - Costa de Oliveira, Vanuze; dos Santos, Anacleto Ranulfo; Santos de Souza, Girlene; Miranda dos Santos, Ricardo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
This study aimed to assess the rates of gas exchange and growth of oregano plants grown in light environments modified with the use of colored screens and organic fertilizer.  Oregano plants with a 90-day cycle were used, obtained with conventional cutting. A completely randomized design with six replications was employed in a 3×4 factorial scheme (two organic fertilizers plus control, and four light environments modified using screens with the colors blue, gray and red plus the control). The oregano plants grown under the blue mesh and fertilized with cattle manure showed a higher number of leaves; the colored screens provided greater stem length and a higher production dry matter; plants grown in full sun showed higher values for gas exchange. It is concluded that the modified light environments and organic fertilizer contributed to the reduction of the gas exchange and favored oregano growth.